2022
DOI: 10.1111/jpi.12812
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mitigates aflatoxin B1‐induced liver injury via modulation of gut microbiota/intestinal FXR/liver TLR4 signaling axis in mice

Abstract: Aflatoxin B1 (AFB1) is a widespread contaminant in foods and feedstuffs, and its target organ is the liver. Melatonin (MT) has been shown to alleviate inflammation in organs and remodel gut microbiota in animals and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…Recently, Mehrzad’s study found that AFB1 exposure (i.e., 10 ng/mL for 12 h) could significantly upregulate the expression of MyD88, NF-κB, tumor necrosis factor-alpha (TNF-α), TLR2, TLR4, cyclooxygenase 2 (COX-2), human leukocyte antigen–DR isotype (HLA-DR), CD209, CD16, C-C motif chemokine receptor 7 (CCR7), and lymphocyte function-associated antigen 3 (LFA3), and it could significantly downregulate the expression of CD11c and CD64, Aryl hydrocarbon receptor (AhR), and transforming growth factor-β (TGF-β) in human dendritic cells, indicating that AFB1 exposure could alter the transcription of key functional immune and inflammatory genes, phagocytosis, and survival of human dendritic cells [ 113 ]. Consistent findings were confirmed in the liver and ileum tissues of mice and liver tissues of chicken [ 34 , 49 ]. Furthermore, AFB1-induced activation of TLR4/NF-κB may be attributed to the production of LPS caused by AFB1-induced gut-microbiota-dysfunction-derived abundance of LPS-producing related bacteria [ 49 ].…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...supporting
confidence: 64%
See 2 more Smart Citations
“…Recently, Mehrzad’s study found that AFB1 exposure (i.e., 10 ng/mL for 12 h) could significantly upregulate the expression of MyD88, NF-κB, tumor necrosis factor-alpha (TNF-α), TLR2, TLR4, cyclooxygenase 2 (COX-2), human leukocyte antigen–DR isotype (HLA-DR), CD209, CD16, C-C motif chemokine receptor 7 (CCR7), and lymphocyte function-associated antigen 3 (LFA3), and it could significantly downregulate the expression of CD11c and CD64, Aryl hydrocarbon receptor (AhR), and transforming growth factor-β (TGF-β) in human dendritic cells, indicating that AFB1 exposure could alter the transcription of key functional immune and inflammatory genes, phagocytosis, and survival of human dendritic cells [ 113 ]. Consistent findings were confirmed in the liver and ileum tissues of mice and liver tissues of chicken [ 34 , 49 ]. Furthermore, AFB1-induced activation of TLR4/NF-κB may be attributed to the production of LPS caused by AFB1-induced gut-microbiota-dysfunction-derived abundance of LPS-producing related bacteria [ 49 ].…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...supporting
confidence: 64%
“…Consistent findings were confirmed in the liver and ileum tissues of mice and liver tissues of chicken [ 34 , 49 ]. Furthermore, AFB1-induced activation of TLR4/NF-κB may be attributed to the production of LPS caused by AFB1-induced gut-microbiota-dysfunction-derived abundance of LPS-producing related bacteria [ 49 ]. An early study found that LPS could enhance AFB1-induced liver toxicity, and this was dependent on the production of TNF-α [ 125 ].…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...supporting
confidence: 64%
See 1 more Smart Citation
“…This may be the result of intestinal inflammation caused by liver fibrosis. In addition, increased intestinal permeability leads to liver toxic substances (such as LPS) entering into the liver [ 45 ] and promotes intestinal bacterial translocation [ 46 ], thereby activating the hepatic inflammatory pathway and aggravating hepatic fibrosis. Nevertheless, the downregulation of glutathione was reversed by TACS intervention, indicating that TACS could ameliorate the disturbed glutathione metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…AFB1 can induce mutations in genomic DNA, and it can lead to neoplastic transformations through the deregulation of epigenetic conditions. 11 The toxic effects of AFB1 on the liver are closely associated with its metabolic activation to the free radical AFB1-exo-8,9-epoxide (AFBO) through the involvement of the cytochrome P-450 enzymes. 12 It is further associated with the formation of ROS, especially the hydroxyl radical (HO.…”
mentioning
confidence: 99%